Formulation and Evaluation of Fast Dissolving Tablets of Taste-Masked Ondansetron Hydrochloride by Solid Dispersion - A. Abdulqader, Alaa; B. H.Al-Khedairy, Eman (Iraqi Journal of Pharmaceutical Sciences, 2017)
Ondansetron hydrochloride (ONH) is a very bitter, potent antiemetic drug used for the treatment and/or prophylaxis of chemotherapy or radiotherapy or postoperative induced emesis. The objective of this study is to formulate and evaluate of taste masked fast dissolving tablet (FDTs) of ONH to increase patient compliance. ONH taste masked granules were prepared by solid dispersion technique using Eudragit E100 polymer as an inert carrier. Solvent evaporation and fusion melting methods were used for such preparation.Completely taste masking with zero release of drug in phosphate buffer pH 6.8was obtained from granules prepared by solvent evaporation method using drug: polymer ratio of 1:2, from which four formulas pass pre-compression evaluation and compressed to FDTs and evaluated for their drug content, in-vitro disintegration time, in-vivo disintegration time, wetting time and in vitro drug release profile.F7 which is prepared from solid dispersion product equivalent to the required dose of ONH , Crosspovidone as superdisintegrant, Aspartame as sweetener ,Ross berry as flavor ,Polyvinylpyrolidone K30.3.as binder ,Avicil PH102 and , mannitol as diluents give best in- vitro, in-vivo disintegration time and best drug release profile.Key words: Ondansetron hydrochloride, taste masking, solid dispersion, Eudragit E100.